Living histories : global conversations in art education - Garnet, Dustin; Sinner, Anita, 1967- (Artwork scholarship, 2022)
This new edited collection explores histories of art education in international contexts. Offers a series of thoughtful and invigorating conversations with international scholars who evoke our conceptualizations of the histories of art education in pursuit of more equitable, diverse and inclusive understandings of the field.